Distribution of unbranched flows with self-similarity effect - Агеев, Дмитрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2013)
An important stage in the design and operation of telecommunication systems is the choice of routes and finding of the intensity of flows along these routes. This problem is known as the problem of the distribution of flows. The existing methods of solution are based on simple flow models, which lost their adequacy for the modern multiservice traffic. The studies have shown that the models of self-similar processes describe more precisely the properties of the traffic. Despite the large number of publications on the self-similar traffic study there is a significant lack of works on the application of these models in the synthesis of telecommunications systems. The article suggests a modification of the previously known method of deflection of unbranched flows taking into account the effect of self-similarity. As a result, in the basic method of calculation we have changed a number of expressions that provide the finding of the parameters of aggregated flows and the average delay in the network. The proposed method can be used when designing large balanced telecommunication systems, where a flow has little influence on the quality parameters of service of the whole network.